Behavioral and genomic characterization of molt-sleep in the tobacco hornworm, Manduca sexta. (July 2015) - MacWilliam, Dyan; Arensburger, Peter; Higa, Jason; Cui, Xinping; Adams, Michael E.
Abstract: During the transition from feeding to molting, larval insects undergo profound changes in behavior and patterns of gene expression regulated by the neuroendocrine system. For some species, a distinctive characteristic of molting larvae is presence of a quiescent state sometimes referred to as "molt-sleep". Here, observations of 4th instar Manduca sexta larvae indicate the molting period involves a predominantly quiescent state that shares behavioral properties of adult insect sleep in that it is rapidly reversible and accompanied by a reduced responsiveness to both mildly arousing and noxious stimuli. When subjected to noxious stimuli, molting larvae exhibit locomotory and avoidance behaviors similar to those of inter-molt larvae. Although less consolidated, inter-molt quiescence shares many of the same behavioral traits with molting quiescence. However, when subjected to deprivation of quiescence, inter-molt larvae display a compensatory rebound behavior that is not detected in molting larvae. This suggests that molting quiescence is a specialized form of inactivity that affords survival advantages to molting larvae. RNA-seq analysis of molting larvae shows general reduction in expression of genes encoding GPCRs and down regulation of genes connected with cyclic nucleotide signaling. On the other hand, certain ion channel genes are up-regulated, including transient receptor potential (TRP) channels, chloride channels and a voltage-dependent calcium channel. These findings suggest patterns of gene expression consistent with elevation of quiescent state characteristic of the molt in a model holometabolous insect. Graphical abstract: Highlights: "Molt-sleep" is a state of consolidated quiescence characterized by rapid reversibility and reduced responsiveness. Molting larvae respond to mild or noxious stimuli with avoidance behaviors similar to those of inter-molt larvae. Molting quiescence differs from conventional sleep in that it lacks a sleep-rebound in response to sleep-deprivation. Molting larvae down-regulate GPCR and cyclic nucleotide genes and up-regulate TRP, chloride, and calcium channel genes.